2014
DOI: 10.1179/1743284713y.0000000341
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive model for AZ31 magnesium alloy based on isothermal compression test

Abstract: Isothermal compression tests at temperatures ranging from 523 to 723 K and strain rates from 0·01 to 10 s−1 were performed on AZ31 magnesium alloy to reveal the deformation characteristics. The flow stress–strain curves show that the flow stress reaches a peak value and then decreases to steady values, which characterise a dynamic flow softening. The measured flow stress was modified by friction and temperature correction, which reflect the friction corrected flow stresses are lower than the measured ones and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Therefore, the flow stress at high strain rates (1 s-1 and 5 s -1 ) must be corrected to account for the temperature rise induced by plastic deformation. The changes of stress caused by temperature rise can be calculated by the following equation (Luan et al, 2014):…”
Section: Stress Correctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the flow stress at high strain rates (1 s-1 and 5 s -1 ) must be corrected to account for the temperature rise induced by plastic deformation. The changes of stress caused by temperature rise can be calculated by the following equation (Luan et al, 2014):…”
Section: Stress Correctionmentioning
confidence: 99%
“…This method indicated that the flow stress at high strain rates must be corrected for the temperature rise induced by plastic deformation. Luan et al (2014) also adopted a similar correction approach in studying the constant temperature extrusion of AZ31 magnesium alloy. In this paper, deformation heat effect and necking played an important role in the analysis of experimental results, so it is necessary to improve on experimental technology.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature correction method uses a linear regression analysis to determine the rate of change of stress with increase in temperature, which is used in conjunction with the target temperature, actual temperature, and recorded stress, to determine what the representative stress will be. This method is described in detail by Luan et al [70], and in this research was applied to any sample which had been compressed with a strain rate of 1.0. Samples tested at lower strain rates did not increase in temperature during deformation, and therefore did not require this correction to be applied.…”
Section: Correction Methodsmentioning
confidence: 99%
“…The stress-strain state during deformation is complex [2], due to inhomogeneities effects of process parameters [4]. Physical simulations using the thermo-mechanical equipment have been applied to predict and simulate the metal forming processes [7][8][9]. Researchers have used different sample geometry size having the same aspect ratio of 1.5 to study the metal flow behaviour [3,9,10].…”
Section: Introductionmentioning
confidence: 99%